Development of Microsoft Powerpoint Learning Media in Science Subjects in Class V in Elementary School - Mamonto, Cici Prishelia; Mutmainah, Mutmainah; Reksamunandar, Rhyan Prayuddy (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Ilmu Keguruan IAIN Manado, 2023)
PowerPoint-based learning media is the development of learning tools by creating presentation slides and integrating various media such as images, animation, and text as teaching materials. Media use in learning activities needs to be done to facilitate the learning process and achieve optimal results from the learning objectives. Therefore, as a component of education, teachers must be more creative and innovative in presenting learning, such as using learning media as teaching materials. This research uses the Borg and Gall model of research development (R&D) methods. The steps in this development research include potential problems, literature study, information gathering, product design, product design validation, and prototype. The feasibility of the product is based on the results of assessments by media experts, material experts, and class teachers as test subjects. Data collection techniques use interviews, questionnaires, and documentation. The results of the research show that the assessment from media experts received a score percentage of 92.22%, including in the very appropriate category, material experts received a score percentage of 96%, including in the very appropriate category, and validation teachers received a presentation score of 96.66%, including in the very appropriate category. It can be concluded that Powerpoint media for science learning at SDN 1 Nonapan II is suitable as teaching material.